The Defense of Waters (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2024)
In Egypt, as early as the Middle Kingdom, the construction of fortresses began to defend the new borders of the empire to the south, placing the new borders of Egypt on the second cataract of the Nile. In fact, the oldest fortresses date back to this period and were built right between the first and second cataracts to have direct control over the river, in particular in the points where the Nile became navigable again in order to better control both the border and the transit of men and goods from south to north. The borders expand not only to the south but also to the east towards the Sinai and to the west towards the Libyan coast and it is here that the sovereigns built a whole series of fortresses to defend the sources of drinking water to allow the armies or merchant caravans to be able to supply water during the long military campaigns in the desert or for the long crossings that awaited the merchants who headed west.
Keywords: Ancient Egypt; Water; Fortresses; Nile; Borders; Trades